Ramadan Courses at Islamic High School Samarinda (Virtues and Practices in the Month of Ramadan): Pesantren Ramadhan di SMA Islam Samarinda (Keutamaan dan Amaliyah di Bulan Ramadhan) - Fuad Fansuri; Siti Sagirah; Mutmainnah; Miftahul Ramadhani; M.Yusuf Qardawi; Dzul Rachman (Journal of Empowerment and Community Service (JECSR), 2023)
Ramadan courses at Samarinda High School is an effort of community service aimed at strengthening spirituality and togetherness during the holy month of Ramadan. In this context, the pesantren activities are not only acts of worship but also means to strengthen Islamic values and social care. This article describes the virtues of the month of Ramadan in Islamic teachings and the implementation of religious activities within the pesantren, such as prayers and fasting, moral development, distribution of iftar meals, collective iftar, religious studies, and religious lectures. Through these activities, the Ramadan Pesantren at Samarinda High School has successfully had positive impacts such as improving the quality of worship, enhancing social relationships, increasing social awareness, and fostering moral development among participants and the surrounding community. Thus, the Ramadan Pesantren at Samarinda High School serves not only as a place of worship but also as a means to strengthen faith, togetherness, and compassion towards others during the blessed month of Ramadan.